Aptamer-based factor IXa inhibition preserves hemostasis and prevents thrombosis in a piglet model of ECMO - Christopher R. Reed; Desiree Bonadonna; James C. Otto; Charles Griffin McDaniel; Charlene Vongai Chabata; Maragatha Kuchibhatla; James Frederiksen; Juliana M. Layzer; Gowthami M. Arepally; Bruce A. Sullenger; Elisabeth T. Tracy (Elsevier, 2022)
Extracorporeal membrane oxygenation (ECMO) requires anticoagulation to prevent clotting when the patient's blood contacts the circuit. Unfractionated heparin (UFH) usually prevents clotting but can cause life-threatening bleeding. An anticoagulant that selectively inhibits the contact activation (intrinsic) pathway while sparing the tissue factor (extrinsic) pathway of coagulation might prevent clotting triggered by the circuit while permitting physiologic coagulation at surgical sites. DTRI-178 is an RNA anticoagulant aptamer conjugated to polyethylene glycol that increases its half-life in circulation. This aptamer is based on a previously described molecule (9.3t) that inhibits intrinsic tenase activity by binding to factor IXa on an exosite. Using a piglet model of pediatric venoarterial (VA) ECMO, we compared thromboprevention and blood loss using a single dose of DTRI-178 versus UFH. In each of five experiments, we subjected two litter-matched piglets, one anticoagulated with DTRI-178 and the other with UFH, to simultaneous 12-h periods of VA ECMO. Both anticoagulants achieved satisfactory and comparable thromboprotection. However, UFH piglets had increased surgical site bleeding and required significantly greater blood transfusion volumes than piglets anticoagulated with DTRI-178. Our results indicate that DTRI-178, an aptamer against factor IXa, may be feasible, safer, and result in fewer transfusions and clinical bleeding events in ECMO.